Heterogenous Weld Heat Resistant Steel With Cobalt Alloy - Sigmund, Marian (Manufacturing Technology Journal, 2021)
The article describes problems of welding heterogeneous welds be specific of heat resistant steel X15CrNiSi20-25 with cobalt alloy Stellite 6. Heterogeneous welds are produced by GTAW (141 according to standard EN ISO 4063) welding method. The major goals of the experiment were performing preliminary welding specifications (pWPS) for a specific welded part. Further was necessary for this weldment set parameters on mechanical testing.
Keywords: GTAW welding (method 141); Heterogeneous weld; pWPS - preliminary welding specification; Cobalt alloy.